Value of Widal Test in the Diagnosis of Typhoid Fever (Medicine Today, 2016)
Typhoid Fever occurs worldwide primarily in developing nations where sanitary conditions are poor. The absence of specific symptoms and signs makes the clinical diagnosis difficult. Definitive diagnosis requires the isolation of S. typhi from blood or other body fluid. But in developing countries culture facilities often not available & diagnosis rely upon clinical features and the detection of antibodies by the Widal test. Numerous studies however have cast serious doubts on the value of the test. The aim of the study was to reassess the utility of a single Widal test in the diagnosis of typhoid fever. The descriptive study was carried out on 100 adult patients with suspected cases of typhoid fever, in the Department of Medicine, Chittagong Medical College Hospital for a period of one year from January to December 2009. Blood samples were collected to perform culture and Widal test. TO titre ?1:160 were considered as significant. AO or BO?1:160 was also considered as significant. The results showed 24 among 100 clinically suspected typhoid fever cases yielded growth of S. typhi. Widal test was found significant in 20(83.33%) out of 24 cultured confirmed cases. Results revealed significant difference in Widal test results between culture positive and negative cases, X2 value 5.601, P value 0.018(